P60 The experience of recruiting hospice patients, family members and health care professionals to a qualitative research study. (1st October 2013) - Perry, Rachel; Orlando, Rosanna; Coast, Joanna; Armour, Kathy
Abstract : Background: A single patient recruitment site hospice and local university partnership has been established for a European Research Council funded research study. It aims to assess the validity of a supportive care measure in patients receiving end of life care, people close to them (CPs) and primary healthcare professionals (HCPs). The recruitment targets are 35 patients, 20 CPs and 20 HCPs. A hospice nurse (HN) identifies participants prior to recruitment by university researchers. Aim: To establish successful patient recruitment in a hospice new to research. Approach Used: The HN liaised with the multidisciplinary team (MDT) to identify eligible patients and provide support; she also approached all eligible patients in her own area of practice, day services. Facilities (e.g. interview rooms) were organised for researchers to recruit and interview participants. Outcomes: To date, 22 patients have been introduced to the study by the HN and given a patient information leaflet. 6 patient follow-ups are pending and 3 interviews have been booked. 5 patients have been recruited from Day Hospice. With permission from patients, 2 CPs and 4 HCPs have been interviewed. Challenges affecting recruitment include environmental issues (moving hospice); ethical issues (amendment required); poor health status of patients and their cyclical involvement in daycare. Remedies include ( i ) dialogue with patients and staff reducing concerns about the research nurse's potential conflict in duties; ( ii ) communication reducing the reluctance of staff to "over-protect" patients and allow recruitment; ( iii ) extension of participants to community and IPU patients improving recruitment rates; (iv) adaptation of patient management system to administer interactions for research. Application to Hospice Practice: Our study explored methods of recruitment of patients to research. Improvements include communication of goals with hospice colleagues and university researchers and a growing confidence in approaching patients. Recruitment experience will change practice in this and future studies.